2021
DOI: 10.5194/aab-64-293-2021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of lifetime productivity traits in goats

Abstract: Abstract. As part of the development of a breeding programme for dairy goats to support sustainable production in organic farming, the overall aim of the present study was to identify traits that can be used as selection criteria for lifetime productivity. The breeding goal is high lifetime productivity with a good milk composition and a good level of robustness in the animals, especially within grazing systems. The lifetime productivity traits analysed in this study were the length of the animal's productive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…Any comparison of the h 2 estimates of longevity from this study with other estimates from other studies of goat is further complicated by the different definitions of longevity and statistical models. To date, except for the Florida breed, the h 2 values for longevity in dairy goats are available using linear models and were clearly lower than ours, ranging between 0.07 and 0.46 (US breeds [34]; UK dairy goats [35]; Saanen and Alpine breeds [36]; German breeds [47]).…”
Section: Genetic Parameterscontrasting
confidence: 58%
See 1 more Smart Citation
“…Any comparison of the h 2 estimates of longevity from this study with other estimates from other studies of goat is further complicated by the different definitions of longevity and statistical models. To date, except for the Florida breed, the h 2 values for longevity in dairy goats are available using linear models and were clearly lower than ours, ranging between 0.07 and 0.46 (US breeds [34]; UK dairy goats [35]; Saanen and Alpine breeds [36]; German breeds [47]).…”
Section: Genetic Parameterscontrasting
confidence: 58%
“…Castañeda-Bustos et al [52] in US dairy goats observed a positive r g for longevity in milk yields ranging between 0.23 and 0.39 and a low r g for female fertility. Wolber et al [47] also observed positive genetic correlation of 0.30 for LPL in milk yield in German goat breeds.…”
Section: Genetic Parametersmentioning
confidence: 86%
“…On chromosome 3 of both ML and GS goats, we identified the MLPH gene ( Figure 4 C), which was characterized as a candidate gene for dilute coat color in some goat breeds [ 45 ]. Additionally, CDKAL1 (FQ) [ 46 ] and POMC (FQ) [ 47 ] were identified as related to weight variation ( Figure 4 D), LIM domain binding 1 ( LDB1 ) and fibroblast growth factor 2 ( FGF2 ) (NL) [ 48 , 49 ] were identified related to high-altitude adaptation ( Table 2 ). Our research also revealed that a specific subset of genes shows pronounced selection signals throughout the local goat breeds from Yunnan province, highlighting the presence of breed-specific selective loci.…”
Section: Resultsmentioning
confidence: 99%